2018
DOI: 10.3390/socsci7030035
|View full text |Cite
|
Sign up to set email alerts
|

An Exploratory Assessment of Community-Oriented Policing Implementation, Social Disorganization and Crime in America

Abstract: Prior research has examined the impact of community-oriented policing (COP) on crime extensively. While the implementation of community policing has been considered mainly within the context of large police agencies, there is a paucity of research on how COP impacts crime reduction efforts in smaller locales. This study explores the effects of the degree of community policing implementation within smaller agencies and cities on crime. As part of the discussion on the impact of COP implementation, this paper al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 48 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…COP emphasizes the development of relationships between the police and stakeholders (Merenda et al, 2020; Uluturk et al ., 2017), and has been shown to be a distinct method of improving police and citizen relationships (Garcia and Polson, 2018; Gill et al ., 2014). These relationships between the police and the community can support crime prevention efforts and/or solve some crimes already committed (Przeszlowski and Crichlow, 2017; Schuck, 2019).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…COP emphasizes the development of relationships between the police and stakeholders (Merenda et al, 2020; Uluturk et al ., 2017), and has been shown to be a distinct method of improving police and citizen relationships (Garcia and Polson, 2018; Gill et al ., 2014). These relationships between the police and the community can support crime prevention efforts and/or solve some crimes already committed (Przeszlowski and Crichlow, 2017; Schuck, 2019).…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
“…Research indicates that the quality of treatment and decision-making during procedurally just encounters drives perceptions of police legitimacy, which ultimately leads to greater levels of compliance and cooperation. To gain collaboration the police must be perceived as fair and honest as well as effective crime fighters (Lytle and Bolger, 2015; Przeszlowski and Crichlow, 2017; Reisig, 2007; Rosenbaum et al ., 2015; Tyler, 2003; Weitzen and Tuch, 2005). According to Tyler (2003), these perceptions of procedural justice can influence satisfaction with police and serve as key antecedents to police legitimacy.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The USA embraced COA strategies from the British system to empower communities to find a lasting solutions to the insecurity posed by high crime rates in the urban areas, especially slums. The popularity of COA in the USA influenced the creation of the Office of Community Policing Services in the mid-1990 [2]. This resulted to police-community partnerships and police transformation through community problem solving initiatives due to decentralization of police services.…”
Section: Introductionmentioning
confidence: 99%
“… 3. In a study of 309 agencies, Przeszlowski and Crichlow (2018) found that only 27% reported implementing multiple comprehensive COP strategies, whereas 77% of agencies implemented at least a few. …”
mentioning
confidence: 99%